Construction of Islamophobia in the USA: Evidence from the Press - Muhammad Tariq (Journal of Peace, Development and Communication, 2022)
The term "Islamophobia" refers to two distinct emotions: anti-Muslim prejudice and anti-Islam sentiments. As relevant literature suggests, these negative feelings are the product of a discourse that portrays Islam and Muslims as a source of fear and insecurity. This study investigated the discursive manifestations of Islamophobia within the theoretical framework of securitization. To investigate these manifestations in the US media discourses, the discourse analysis method was adapted from the DHA. The researcher analyzed a total of 3153 news and opinion articles from US newspapers and wire services between November 2016 and January 2017. This analysis found that both types of negative posturing are present in the US press discourse, which presents the picture of an Islamophobia society. The study concluded that Islamophobia in the US context is primarily a political construct, used to mobilize societal hatred against Islam and Muslims, with hate crimes against Muslims being the most apparent manifestation. The researcher recommends similar inquiry into other contexts as well.